The use of sertraline to treat an adolescent of dystonia comorbid with major depressive disorder with psychotic features - Chia‐Chien Liu; Chen‐Chia Lan; Ying‐Sheue Chen (Wiley, 2024)
Abstract Dystonia is characterized by sustained or intermittent involuntary muscle contractions. Psychiatric symptoms are essential non‐motor features of dystonia, and higher risks of depressive and anxiety disorders have been reported. The precedence of psychiatric to motor symptoms in some patients and the dopaminergic and serotonergic system involvement in both the motor and psychiatric aspects suggest these psychiatric disorders may be intrinsic to the neurobiology of dystonia. Nevertheless, psychiatric comorbidities are often construed as secondary reactions to motor disabilities and the negative bio‐psycho‐social impacts of dystonia, leading to underdiagnosis and undertreatment. Research on antidepressant use in dystonia is scarce, especially in children and adolescents. This report presents a 17‐year‐old female with dystonia comorbid with depression with psychotic features, whose motor symptoms improved but psychiatric symptoms persisted with dopaminergic pharmacotherapy. Sertraline was finally added 5 years after the onset and successfully managed her psychotic depression without worsening motor symptoms. Early detection, prompt diagnosis, and timely holistic treatment with dopaminergic agents, antidepressants, and psychosocial interventions are critical for the mental health of dystonia patients.